Transactional Analysis Counseling to Improve Intercultural Communication of Tourism Vocational Students - Putu Ari Dharmayanti; Adi Atmoko; Blasius Boli Lassan; Muslihati; Putu Sri Lestari (Mimbar Ilmu, 2023)
Schools had never implemented special techniques in the implementation of Guidance and Counseling to develop students' intercultural communication at school. These problems cause failure in the communication process which can result in worsening social relations between students. The aim of this research is to analyze the differences in intercultural communication between Tourism Vocational School students before and after the transactional analysis counseling intervention. The research design used is a pretest posttest group design. The sampling technique in this research is purposive sampling, namely sampling based on the researcher's judgment. This research uses two types of instruments, namely: (1) transactional analysis counseling module treatment materials, and (2) data collection instruments in the form of an intercultural communication competency scale. The data collected in this research is then analyzed using the non-parametric Wilcoxon statistical test. To answer the hypothesis in this research, it can be seen from the results of the pretest and posttest hypothesis test table which shows a significance figure of 0.028 which means less than 0.05 so that Ho is rejected, so the hypothesis is accepted, namely that there is a difference in intercultural communication between Tourism Vocational School students before the transactional analysis counseling intervention and after intervention in the experimental group.